ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA PERUSAHAAN PADA PT UNILEVER INDONESIA TBK PERIODE 2012-2016 - Alcianno G. Gani (JURNAL MITRA MANAJEMEN, 2020)
ABSTRACTThe purpose of this study to determine the financial performance of PT Unilever Indonesia Tbk period 2012 to 2016 based on financial ratio analysis. The method used is descriptive method with quantitative analysis. The results obtained from this research is the Performance of PT Unilever Indonesia Tbk based on the liquidity ratio is not good, because the current ratio of companies in 2012 to 2016 less than 100%. In the year 2012 by 67%, 2013 by 70%, 2014 by 71%, 2015 by 65%, and by 2016 by 61%. PT Unilever Indonesia Tbk's solvency ratio in 2012 until 2016 is good because the company's Long Term Debt to Equity Ratio in 2012 up to 2016 is less than 100%. In 2012 by 12%, 2013 by 15%, 2014 by 14%, 2015 by 16%, and by 2016 by 24%. This means that the company is able to guarantee long-term debt with the company's capital. PT Unilever Indonesia Tbk's profitability ratio in 2012 up to 2016 is not good because its operating profit margin decreases. In 2012 by 24%, 2013 by 23%, 2014 by 23%, 2015 by 21%, and by 2016 by 21%. PT Unilever Indonesia Tbk Activity Ratio in 2012 until 2016 is good because the company's receivable turnover is always above angaka at least 12 times only in 2013 under minimum 12 times. 12.12 times for 2011, 10.99 times for 2012, 14.01 times for 2013, 12.92 for 2014, and 12.12 for the year 2016. Keywords: Financial Ratios, Liquidity, Solvency, Profitability, Activity